Neuroprotective Potential of Tamarillo (Cyphomandra betacea) Epicarp Extracts Obtained by Sustainable Extraction Process - Zully Jimena Suárez-Montenegro (Frontiers Media S.A., 2021)
Tamarillo (Cyphomandra betacea (Cav.) Sendt.), or tree tomato, is a tropical fruit from the Andean region of South America; it is highly rich in vitamins, minerals, and polyphenolic compounds. In this study, extracts from tamarillo epicarp (TE) were obtained by pressurized liquid extraction (PLE), and their in-vitro neuroprotective potential was assessed. A central composite design with response surface methodology was performed to optimize PLE as a function of solvent composition and temperature. Selected response variables were extraction yield, total phenolic content (TPC), total flavonoid content (TFC), total carotenoid content (TCC), antioxidant (ABTS), and anti-inflammatory (LOX) activities, and anti-acetylcholinesterase (AChE) inhibitory capacity. According to the desirability function, the optimal conditions were 100% ethanol and 180°C with a 0.87 desirability value. Next, the anti-butyrylcholinesterase enzyme (BChE), reactive oxygen species (ROS), and reactive nitrogen species (RNS) inhibition as well as cytotoxicity in HK-2, THP-1 monocytes, and SH-5YSY neuroblastoma cell lines were studied for the TE extract obtained under optimized conditions. The optimum TE extract provided the following results: extraction yield (36.25%), TPC (92.09 mg GAE/g extract), TFC (4.4 mg QE/g extract), TCC (107.15 mg CE/g extract), antioxidant capacity (ABTS, IC50 = 6.33 mg/ml extract), LOX (IC50 = 48.3 mg/ml extract), and AChE (IC50 = 97.46 mg/ml extract), and showed no toxicity at concentration up to 120 μg/ml extract for all the tested cell lines. Finally, chemical characterization by liquid chromatography-tandem mass spectrometry (UHPLC-q-TOF-MS/MS) of the optimum TE extract exhibited an important presence of hydroxycinnamic acid derivatives and other phenolic acids as well as quercetin hexoside and rutin, as main metabolites responsible for the observed biological properties. All these results suggested that TE, which represents between 8 and 15% of the total fruit, could become a promising natural by-product with a potential “multitarget” activity against Alzheimer's disease.